Digital Microfluidics: Paper‐Based Digital Microfluidic Chip for Multiple Electrochemical Assay Operated by a Wireless Portable Control System (Adv. Mater. Technol. 3/2017). Issue 3 (March 2017) - Ruecha, Nipapan; Lee, Jumi; Chae, Heedo; Cheong, Haena; Soum, Veasna; Preechakasedkit, Pattarachaya; Chailapakul, Orawon; Tanev, Georgi; Madsen, Jan; Rodthongkum, Nadnudda; Kwon, Oh‐Sun; Shin, Kwanwoo
Abstract : In article number 1600267, Nadnudda Rodthongkum, Oh‐Sun Kwon, Kwanwoo Shin, and co‐workers report the development of a paper‐based active microfluidic lab‐on‐a‐chip implemented with electrochemical sensors on a portable electrical control system. By varying the sensor modules, a multiple detection of three diagnostic biological molecules is demonstrated. With a newly designed portable power supply and wireless control system, this active paper‐based chip platform can be utilized as an advanced point‐of‐care device for multiple assays in digital microfluidics.